A study on the performance of students of the kulliyyah of economics and management sciences in quantitative subjects - Larbani, Moussa (s.n, 2012)

(untitled)
The Kulliyyah of Economics & Management Science (KENMS)management had been receiving casual complaint from students and lectures about the performance of quantitative courses in the Kulliyyah. Accordingly, the Dean, Prof. Dr. Khalid Ahmad, commissioned Prof. Dr. Moussa Larbani to conduct a study on the subject. Prof. Dr. Moussa (principal Researcher) later formed a research team and included Asst. Prof. Dr. Mustafa Omar Mohammed as a Co-Researcher. A survey of previous studies conducted in other institutions of learning and time series data of students performance in KENMS and Centre Foundation Studies (CFS) have been used to justify the rational for the study.